The Phenomenon of Violence Against Women and Children in Households - Mulyadi, Eko Syukri; Aziz, Hasnah; Humulhaer, Siti (Jurnal Ius Constituendum, 2024)
This research aims to conduct a study and conduct more in-depth research regarding the phenomenon of domestic violence that occurs in the Tangerang City community. The background to the problem in this writing is that there are still many cases of domestic violence that occur in Tangerang City, there are people who have reported it but there are still many who have not reported it because of threats from their husbands, embarrassment, and so on. Therefore, this writing has an urgency that must be discussed and studied in depth by conducting research on various institutions that handle cases of domestic violence in Tangerang City. This research method uses a qualitative juridical method using data collection in the form of observations, interviews, and documents carried out at the Tangerang City Metro Police, the Tangerang City Women's Empowerment, Child Protection, Population Control, and Family Planning (DP3AP2KB) Service, the Tangerang City Women's Empowerment and Child Protection Integrated Service Center (P2TP2A), and the Tangerang City District Court. The results of the research and discussion are that the violence that often occurs is physical violence, sexual violence, physical violence, and child neglect. The factors that cause this include economic factors, infidelity factors, educational factors, and employment factors. Efforts made to prevent domestic violence include education and outreach on violence against women and children in schools, Islamic boarding schools, and universities.